Overview of the Mechanisms that May Contribute to the Non-Redundant Activities of Interferon-Inducible CXC Chemokine Receptor 3 Ligands - Metzemaekers, Mieke; Vanheule, Vincent; Janssens, Rik; Struyf, Sofie; Proost, Paul (Frontiers in Immunology, 2018)
The inflammatory chemokines CXCL9, CXCL10 and CXCL11 are predominantly induced by interferon (IFN)-γ and share an exclusive chemokine receptor named CXCR3. With a prototype function of directing temporal and spatial migration of activated T cells and natural killer (NK) cells, and inhibitory effects on angiogenesis, these CXCR3 ligands have been implicated in infection, acute inflammation, autoinflammation and autoimmunity, as well as in cancer. Intense former research efforts led to recent and ongoing clinical trials using CXCR3 and CXCR3 ligand targeting molecules. Scientific evidence has claimed mutual redundancy, ligand dominance, collaboration or even antagonism, depending on the (patho)physiological context. Most research on their in vivo activity, however, illustrates that CXCL9, CXCL10 and CXCL11 each contribute to the activation and trafficking of CXCR3 expressing cells in a non-redundant manner. When looking into detail, one can unravel a multistep machinery behind final CXCR3 ligand functions. Not only can specific cell types secrete individual CXCR3 interacting chemokines in response to certain stimuli, but also the receptor and glycosaminoglycan (GAG) interactions, major associated intracellular pathways and susceptibility to processing by particular enzymes, amongst others, seem ligand-specific. Here, we overview major aspects of the molecular properties and regulatory mechanisms of IFN-induced CXCR3 ligands, and propose that their in vivo non-redundancy is a reflection of the unprecedented degree of versatility that seems inherent to the IFN-related CXCR3 chemokine system.